Inserções de história da matemática em livros didáticos de matemática dos anos finais do ensino fundamental - Teixeira, Wilza Maria Adão Lopes (2023)
The integration of the history of mathematics into mathematics teaching is a topic that has been much debated in recent decades. In Brazil, thanks to the Programa Nacional do Livro Didático (PNLD - Brazilian Textbook Program), many students and teachers in the public school system have access to the history of mathematics included in textbooks. This research has the general objective of mapping and describing the insertions of the history of mathematics in three collections of mathematics textbooks for the final years of Elementary School, approved by the PNLD 2020. With a qualitative and quantitative approach, the methodology of this investigation is based on documentary and bibliographical research, to carry out a brief review of previous research and to analyze the insertions. The documentary corpus of the research is formed by the collections: A Conquista da Matemática, Matemática Bianchini, and Teláris Matemática, which were the collections of Mathematics textbooks with the largest number of copies acquired by the government in the edition of the PNLD 2020. For data collection, first, the insertions of History of Mathematics in the 12 books were identified. Then, the data were registered through a form, applied via Google Forms. 219 insertions were identified in the analyzed books. Among the results, it is highlighted that the territory most mentioned in the insertions is the European continent, at different times. Mostly, the contributions of European men in the development of mathematics are highlighted. Only one female mathematician was cited. Thus, the history of mathematics portrayed in the analyzed collections is mostly male, white, and European. The insertions are well illustrated, the most registered content in the images was paintings portraying historical characters. The mathematical content that most evoked insertions was numbers and operations. Most insertions have a narrative focused on just one historical episode; however, there are many insertions that cover several episodes, citing different historical periods, locations, or civilizations. A very positive result is the number of insertions classified as HdM and didactic strategy. Such insertions can help in the development of some mathematical reasoning in the student, through history. It is hoped that the results of this research can point to new directions for the challenge of integrating history and mathematics teaching and can contribute to a more critical look at this integration.